The bank lending channel in a dual banking system: Evidence from Malaysia - Guglielmo Maria Caporale; Abdurrahman Nazif Çatık; Mohamad Husam Helmi; Faek Menla Ali; Mohammad Tajik (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper examines the bank lending channel of monetary transmission in Malaysia, a country with a dual banking system including both Islamic and conventional banks, over the period 1994:01-2015:06. A two-regime threshold vector autoregression (TVAR) model is estimated to take into account possible nonlinearities in the relationship between bank lending and monetary policy under different economic conditions. The results indicate that Islamic credit is less responsive than conventional credit to interest rate shocks in both the high and low growth regimes. By contrast, the relative importance of Islamic credit shocks in driving output growth is much greater in the low growth regime, their effects being positive. These findings can be interpreted in terms of the distinctive features of Islamic banks.
Keywords: C32; E31; E42; E58; 330; Bank lending channel; Malaysia; Monetary transmission; Threshold VAR